Microbial shelf life quality assessment of a sensory evaluated ready-to-serve Momordica charantia L. (Bitter Gourd) drink - Chern, Pei Ern; Mahyudin, Nor Ainy; Mohd Ghazali, Hasanah; Mahmud @ Ab Rashid, Nor Khaizura (Open Science Publishers, 2018)
The bitter gourd, Momordica charantia L. (MC), is used to prepare a ready-to-serve (RTS) drink. The objective is to evaluate the sensory characteristics of the drink according to consumer acceptability and to investigate its microbial shelf life when prepared using untreated and boiled water and stored at different temperatures. MC was used to prepare five concentrations of RTS drink (0.58, 0.70, 0.80, 0.90, and 1.00 g/mL) by water extraction of juice added with selected ingredients. The samples were given to 40 untrained panelists and are rated on a 7-point hedonic scale. Total plate count, enumeration of yeasts and molds and presumptive tests for coliform count and Escherichia coliwere used in assessing the microbial quality. From the sensory evaluation, the most accepted concentration of the RTS drink is 0.80 g/mL with an average score of 4.09. High amount of microbial growth exceeding 4 log CFU/mL was found after 24 h when stored at 28 ± 2°C. Mold growth was visible when stored at 28 ± 2°C after 48 h. E. coliwas presumptively present in the sample but not in water used for preparation. This formulation of RTS drink can be beneficial for targeted consumers and ensuring the microbial safety through proper production and storage.